2023
DOI: 10.1186/s12906-023-03891-3
|View full text |Cite
|
Sign up to set email alerts
|

Experience of parents in delivering pediatric tuina to children with symptoms of attention deficit hyperactivity disorder during the COVID-19 pandemic: qualitative findings from focus group interviews

Abstract: Background Evidence suggests that pediatric tuina, a modality of traditional Chinese medicine (TCM), might have beneficial effects on the symptoms of attention deficit hyperactivity disorder (ADHD), such as overall improvements in concentration, flexibility, mood, sleep quality, and social functioning. This study was conducted to understand the facilitators and barriers in the delivery of pediatric tuina by parents to children with ADHD symptoms. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…A study comparing face-to-face focus group and online focus group discussions via 16 interview sessions (a total of 48 participants) found that the online focus group communication generated a high volume of ideas and solutions [42]. In our previous study, we also conducted online focus group interviews for qualitative data collection and examined their feasibility, convenience, and safety during the pandemic [43]. This strategy can enable the participation of an adequate number of CM practitioners, and the interviews were conducted in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing face-to-face focus group and online focus group discussions via 16 interview sessions (a total of 48 participants) found that the online focus group communication generated a high volume of ideas and solutions [42]. In our previous study, we also conducted online focus group interviews for qualitative data collection and examined their feasibility, convenience, and safety during the pandemic [43]. This strategy can enable the participation of an adequate number of CM practitioners, and the interviews were conducted in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using online focus groups because they may be an effective way to solicit public opinion on health and medical issues, especially from diverse and geographically dispersed participants [39]. The focus groups were conducted through Voov Meeting (Tencent Ltd), the most used online meeting platform in mainland China, which allows for instant communication and enables the moderator to coordinate the entire discussion process appropriately [40].…”
Section: Data Collectionmentioning
confidence: 99%
“…Consequently, current guidelines and practices increasingly focus on nonpharmacological treatments such as massage or Tui na [4,17]. Pediatric Tui na, based on the principles of the meridian theory [18] of traditional Chinese medicine (TCM) [19], is widely used as a complementary and alternative medicine in East Asia [20][21][22][23]. It treats a range of pediatric diseases by applying various manipulations on the body surface, including pressing, kneading, circling, nipping, and pushing [24,25].…”
Section: Introductionmentioning
confidence: 99%